Studying the impact of an energy retrofit of a UAE-based existing building by adding intelligent valves on the main chilled water risers and reconfigure the chilled water pumps to be on variable water flow loop configuration - MAHMOUD, ABDALLAH (2021)
Buildings’ retrofit has been evolving throughout the past decades worldwide, aiming to improve the overall efficiency of the buildings and its operations, and many owners on private and public sectors are looking for highly effective systems and systems’ components to operate and manage their building stock due to the excessive energy consumption, thermal comfort, indoor air quality and hygienic requirements. This research is going to provide practical insights in building technologies, what multiple attempts have been evolving to improve HVAC systems, either from the effectiveness of heating and cooling distribution systems designs and retrofits or from the system components and operational strategies and techniques, particularly on the chilled water loops’ configuration retrofit and temperature difference “ΔT”. Such retrofit debates have been going into many experimental methods, on-premises’ solutions, new technologies, and multiple techniques of operations, and many guidelines have been published and shared for the sake of continuous improvement of chilled water systems and the optimum ways of operations and to clear those doubts surrounding those kinds of debates, this dissertation is verifying couple of those retrofit measures. With that being said, this research aims to provide reliable information and outputs on the best practice of operating chilled water network for a UAE-based building by converting the constant primary network to a variable one in addition to solve permanently the building ΔT issues by replacing the conventional pressure dependent control valves and adding intelligent valves on the main risers and the main airside equipment for this selected building, aiming to be quite practical as could as possible and have the outcome of combining both measures together, accordingly, the results show a potential energy saving on the range of 14-21% on the conservative side by applying the suggested retrofit measures, which leads to approximately an energy cost of savings of at least half a million to seven hundred thousands of UAE dirhams along with simple payback of 3-4 years which is considered an attractive SPB period for investors on such fields. Such energy cost savings is derived as a result of the significant reduction on pumping capacity in addition to insignificant but noticeable reduction on the lift of the air-cooled chillers’ compressors. Additionally, the research tries to present to buildings’ retrofit community a methodology to be followed for any future attempts on the same field by utilizing computer-based modeling software “IESVE” to simulate the existing cases and compare multiple scenarios for chilled water loops and ΔT. As a result of this research, it is made proven to any debates that retrofitting a typical UAE building by converting constant primary pumps into variable loop in addition to limiting the ΔT between 6 to 9oC on the risers side should lead to a magnificent energy cost saving.